BMT310- Bacteriology (Bakteriologi) - PPSKJ, Pusat Pengajian Sains Kajihayat (Pusat Pengajian Sains Kajihayat, 2024)
First Semester Examination 2023/2024 Academic Session February 2024 BMT310- Bacteriology (Bakteriologi) Duration: 2 hours (Masa: 2 jam)